2021
DOI: 10.1002/advs.202101848
|View full text |Cite
|
Sign up to set email alerts
|

A CD10‐OGP Membrane Peptolytic Signaling Axis in Fibroblasts Regulates Lipid Metabolism of Cancer Stem Cells via SCD1

Abstract: Carcinoma-associated fibroblasts (CAFs) consist of heterogeneous subpopulations that play a critical role in the dynamics of the tumor microenvironment. The extracellular signals of CAFs have been attributed to the extracellular matrix, cytokines, cell surface checkpoints, and exosomes. In the present study, it is demonstrated that the CD10 transmembrane hydrolase expressed on a subset of CAFs supports tumor stemness and induces chemoresistance. Mechanistically, CD10 degenerates an antitumoral peptide termed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 136 publications
0
20
0
Order By: Relevance
“…Subtype 2 exhibited a lower proportion of fibroblasts and a higher proportion of proliferating T cells and macrophages. Cancer-associated fibroblasts (CAFs) are not only important components of the BC microenvironment and are essential in tumor growth and development, but also have complex phenotypes and functional heterogeneity [ 56 , 57 , 58 , 59 ]. T cell proliferation is closely related to immune response, treatment resistance, and prognosis of BC [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subtype 2 exhibited a lower proportion of fibroblasts and a higher proportion of proliferating T cells and macrophages. Cancer-associated fibroblasts (CAFs) are not only important components of the BC microenvironment and are essential in tumor growth and development, but also have complex phenotypes and functional heterogeneity [ 56 , 57 , 58 , 59 ]. T cell proliferation is closely related to immune response, treatment resistance, and prognosis of BC [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCD1 is a central lipogenic enzyme that catalyzes the synthesis of monounsaturated fatty acids (MUFA) during lipogenesis in human [41], and it was significantly downregulated after the KO of HIF-1α. SCD1 is known to play an essential role in the progression of cancers [42]. Gao et al found that SCD1 promoted the stemness of ovarian cancer stem cells through the Hippo/YAP pathway [43].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated lipid metabolism is crucial for maintaining CSC stemness properties and fulfilling their energy demands [30,31]. CSC fate decision is reliant on the activity of enzymes involved in lipid metabolism, such as SCD1 [32]. SCD1 is a key enzyme to convert saturated fatty acids into monounsaturated fatty acids (MUFAs), which is involved in the tumorigenesis of multiple cancers, including gastric cancer [33].…”
Section: Discussionmentioning
confidence: 99%